The effect of residual stresses on the formation of transverse cracks in adhesive joints for wind turbine blades. (15th May 2019) - Jørgensen, Jeppe B.; Sørensen, Bent F.; Kildegaard, Casper
Abstract: Transverse cracks in adhesive bonded joints evolve typically due to a combination of mechanical- and residual stresses. In this paper, a new approach that allows the residual stress to be determined on a single test specimen in several different ways is presented. The residual stress measurements were used in combination with a bi-material model to predict the stress at first transverse crack in the adhesive layer of a sandwich specimen (laminate/adhesive/laminate). The model prediction was consistent with measurements from quasi-static tensile tests of the sandwich specimens. These experimental results showed that higher post curing temperature and lower test temperature had a negative effect on the formation of transverse cracks in the adhesive layer i.e. residual stresses were higher and transverse cracks initiated at lower applied mechanical loading. The effect of increased laminate thickness was found to be small under both static and cyclic loading of the sandwich specimens. Furthermore, the cyclic loaded tests confirmed that the design of the sandwich specimen was damage tolerant since multiple cracking of the adhesive developed in a stable manner.